2023
DOI: 10.1038/s41586-023-06634-z
|View full text |Cite
|
Sign up to set email alerts
|

The burden and dynamics of hospital-acquired SARS-CoV-2 in England

Ben S. Cooper,
Stephanie Evans,
Yalda Jafari
et al.

Abstract: Hospital-based transmission had a dominant role in Middle East respiratory syndrome coronavirus (MERS-CoV) and severe acute respiratory syndrome coronavirus (SARS-CoV) epidemics1,2, but large-scale studies of its role in the SARS-CoV-2 pandemic are lacking. Such transmission risks spreading the virus to the most vulnerable individuals and can have wider-scale impacts through hospital–community interactions. Using data from acute hospitals in England, we quantify within-hospital transmission, evaluate likely pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Among 136 NHS acute trusts, we identified that nosocomial infections accounted for 2.9% to 3.5% of the total 106,377 hospitalised COVID-19 patients from October 2020 to March 2022. These estimates are around 1% higher than a previous estimate of nosocomial infections in England between June 2020 and March 2021 [28] but dramatically lower than reported from other studies that focused on the early days of the pandemic [3, 2931]. The reported number of LFD tests from NHS acute trusts was likely to be an underestimate of the actual number of tests performed.…”
Section: Discussionmentioning
confidence: 55%
“…Among 136 NHS acute trusts, we identified that nosocomial infections accounted for 2.9% to 3.5% of the total 106,377 hospitalised COVID-19 patients from October 2020 to March 2022. These estimates are around 1% higher than a previous estimate of nosocomial infections in England between June 2020 and March 2021 [28] but dramatically lower than reported from other studies that focused on the early days of the pandemic [3, 2931]. The reported number of LFD tests from NHS acute trusts was likely to be an underestimate of the actual number of tests performed.…”
Section: Discussionmentioning
confidence: 55%
“…The adaptability of certain emerging pathogen [53], especially in specific areas of hospital [54], provides the pathogen's ability to penetrate the dynamics of hospital's prevention measures, for example in case of SARS-CoV-2 [55] regarding both the risk of exposure to accompanying caregivers that to look after the patients during their hospitalization [56] and the need to maintain quality of care, while at the same time, ensuring all the staff ready to serve and well prepared [57]. Hospital staff (not limited to doctors and nurses) contribute actively to the prevention and management of HAI [57,58] as they are involved in basic personal hygienic care of the patient [59], navigating and implementing quality improvement initiatives [60], conducted necessary automating surveillance [61] via correct microbiological sampling [62], and features of rigid antibiotic stewardship [63].…”
Section: Route Of Transmissionmentioning
confidence: 99%
“…Cooper et al point out that hospitalised patients are especially vulnerable to COVID-19-associated complications and that controlling the transmission of COVID-19 in healthcare settings is critical to reduce the burden of this infection. They also emphasise the lack of studies that consider the effectiveness of vaccines (VE) against COVID-19 in hospitalized patients [ 13 ]. In order to generate real-life evidence on the safety and effectiveness of vaccines in use, the ECDC and the European Medical Agency officially established and launched consistent protocols to design necessary studies [ 14 ].…”
Section: Introductionmentioning
confidence: 99%